Color Vision Impairment in School Children - Moudgil, T.; Arora, R.; Kaur, K. (Highlights on Medicine and Medical Research Vol. 15, 2021)
Background: Prevalence of Color vision impairment is 3- 4 % in India and it goes undetected till later in life as people develop certain adaptations to cope up to certain extent and while some remain unaware of the disease . Objective: To find out the prevalence rate of color vision impairment in students of ages 6 years to 15 years, in various schools of Jalandhar. Methods: A prospective community based study was done on 5000 students to identify the prevalence of color vision impairment. Students were examined with Ishihara Pseudoisochromatic Color Plates 38 edition. If the student was color vision impaired, then it was further classified into its types. The data collected was complied and analyzed to evaluate the prevalence of color vision impairment, gender wise prevalence and prevalence of types of color vision impairment. Results: Students in age group 6-15 years of 15 schools were screened. A total of 5000 students were included in the study; 2022(40.44%) were males and 2978 (59.56%) females. Colour vision impairment was seen in 85 students (1.7%) including 79 (1.58%) males and 6(0.12%) females. Among the colour vision impaired 79(92.94%) were protanopes, 6(7.05 %) were deuteranopes and none were tritanope. Among the protanopes, 75(94.94%) were males and 4 (5.06%) were females and in deuteranopes, percentage of males affected was 4(66.7 %) and females was 2(33.3%). Conclusion: Color vision impairment is more commonly seen in males more than females. Amongst the type of color vision impairment, Protonopia is more common than deutronopia. Tritanopia was not reported in our study. Early school screening for color vision impairment is strongly recommended.